Genome damage and genetic manipulation. Unbalance in public policies priority - Prieto González, Elio A. (Acta Bioethica, 2007)
Unbalance in the treatment of two topics related to the conservation of the human genome integrity is analyzed here: the technologies for genetic manipulation and genome damage due to environmental pollution. Lack of education and of information based on real facts, and the media sensationalist treatment, among other factors, provoke an unbalance between the media agenda and public needs. This leads to a lack of citizenship consciousness over the true threats that genetic material faces and the health risks that it involves.